ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEGAWAI MELAKUKAN TINDAKAN WHISTLE-BLOWING DENGAN REWARD MODEL SEBAGAI VARIABEL MODERATING - Siti Aliyah; Ichwan Marisan (Jurnal Dinamika Ekonomi & Bisnis, 2017)
This study aims to examine the influence of attitude on whistle-blowing, organizational commitment, personal cost, and the seriousness of fraud against the whistle-blowing interests of civil servants in Jepara regency government with rewards model as moderating variables. The data used in the research is the primary data collected through a questionnaire survey. The population is all Civil Servants (PNS) consisting of 1718 people working in the 30 local administrations’ working unit (SKPD) in Jepara regency. With simple random sampling calculated by the Slovin formula, it is obtained 95 people as sample. The analysis technique used is by using Moderating Regression Analysis (MRA). The results of this study show that personal cost and the seriousness of fraud affect significantly on employee’s interest in doing whistle blowing partially, while attitude and organizational commitment variable have no significant effect. The rewards model is not able to moderate the influence of four independent variables on the employee’s interest in doing whistle blowing.